Inertial effect on concrete-like materials under dynamic direct tension. Issue 3 (September 2018) - Zhang, Shu; Lu, Yubin; Jiang, Xiquan; Jiang, Wei
The inertial effect on the dynamic strength enhancement of concrete-like materials has been widely concerned and its influence on the dynamic tensile strength is particularly controversial, causing great disturbance to dynamic measurement. Therefore, both the experimental and the numerical analyses on the tubular specimens of concrete-like materials are conducted to further investigate the degree of inertial effect under dynamic direct tension. The inertial effect is one of the structural effects, and therefore the tubular specimens with different inner diameters are employed to demonstrate the different influences of inertial effect on the dynamic tensile strength of concrete-like materials. The experimental and numerical results indicate that the inertial effect has some influence on dynamic tensile strength, which increases with strain rate. In addition, the surface area of concrete-like materials will be greatly affected by inertial effect under dynamic tensile loading.